Implementasi Metode Pembelajaran Interaktif untuk Meningkatkan Rasa Percaya Diri Siswa di SD Sumber Dumpyong 3, Kabupaten Bondowoso - Dionisius Primario Migo Segu; Nabila Zhaiyan Nazhifa; Putri Wibi Lintang Eristian; Intan Nur Olivia; Nessa Khaira; Zahra Jihan Putri Heldiyanto; Afton Al Habsyi; Agung Nugroho Puspito (Jurnal Pengabdian Nasional (JPN) Indonesia, 2026)
Self-confidence is an important psychological factor that influences elementary school students' participation and courage in the learning process. However, teacher-centered learning often limits students' active involvement, resulting in low self-confidence, especially in oral communication. This community service activity aims to analyze the effect of interactive learning on increasing students' self-confidence at Sumber Dumpyong 3 Elementary School in Bondowoso Regency. The activity was carried out using a pretest-posttest design with a descriptive quantitative approach. There were 40 students in grades I-VI, aged 7-12 years, who participated in the activity. The interactive learning intervention was carried out during the period of August 30 to October 17, 2025, with a duration of 2 × 35 minutes for each learning session. Self-confidence was measured using a closed questionnaire consisting of 10 statements in the pretest and 10 statements in the posttest, with a maximum total score of 40. Data analysis was performed by calculating the average score and normalized gain (N-gain) to determine the increase in students' self-confidence after the intervention. The results showed a pretest average score of 22.71, which increased to 30.22 on the posttest. The N-gain calculation yielded a value of 0.30, which falls into the moderate category. These findings were supported by classroom observations that showed an increase in students' courage to ask questions, participate in discussions, and express their opinions. Thus, interactive learning has been proven to have a positive impact on strengthening the self-confidence and participation of elementary school students, although a longer intervention period is needed to achieve optimal improvement.